Preventing Radicalism Through The Values of Pancasila and Instilling the Value of Character in Young Citizens - Keraf, Fransiskus Markus Pereto; Kollo, Fredik Lambertus (Universitas Malikussaleh, 2019)
The purpose of this study is to determine the role of teachers in instilling the values of Pancasila and the character of the students (young citizens) in Atambua junior high school. Atambua is one of regencies in East Nusa Tenggara province which borders between the State of Indonesia to Timor Leste. Based on observations of researchers that in Atambua junior high school, Civics teachers play an active role in instilling the values of nationalism character in students. Pancasila as a guide to life in Indonesia so it is important to preserve. Efforts to strengthen the values of Pancasila by civics teachers during the learning process. The object of research in Atambua junior high school. The method used in this research is qualitative descriptive form. The results show that teachers strive to instill nationalism Civics on student Atambua junior high school. The technique used by civics teachers in instilling nationalism is to engage students in the class to play drama. Drama prepared by the teacher and played by students. The play contains the living example with berpadomana on Pacasila values, sense of responsibility, nationalism, and self-confidence as a citizen of Indonesia. After the students play the drums, the teacher asks the students to conclude messages and images in the drama. In addition, one of the efforts that teachers do is to always provide various examples of harmony in the lives of diverse ethnic, religious and cultural.